STRATEGI PERCETAKAN UNTUK MENGATASI LONJAKAN PERMINTAAN SELAMA MUSIM PEMILU. STUDI KASUS DARI INDUSTRI PERCETAKAN BANDUNG - Anwar Maulana; Ageng Saepudin Kanda (CV. ALIM'SPUBLISHING, 2024)
Elections are an important moment in the democratic life of a country, when citizens have the opportunity to choose their own leaders and representatives. The campaigns carried out play a role in printing which plays an important role in delivering campaign materials such as leaflets, posters, banners and booklets. Therefore, now that it is the digital era, many printing industries are also facing various challenges and intense competition with their competitors. Then, in terms of marketing, the printing industry must pay attention to its strengths and threats, such as environmental, technological and other factors in facing this election. Therefore, the research that will be carried out aims to examine the marketing strategies used by the printing industry so that it can outperform the competition and what strategies will be implemented if there is a surge in demand. The method used for this research is a qualitative method, which means the researcher analyzes in detail a problem with the printing industry. The researcher used observation and interview techniques for data collection techniques in the printing industry so that they could analyze and collect data in detail. The results of this research are that the MD Draftika printing industry took part in the auction conducted by the KPUD by choosing the place, time and maximum promotion on social media. As a strategy to deal with the surge in demand, MD Draftika made changes to operational hours, added machine technology, added temporary additional employees and maximized supplies of raw materials from suppliers. Keywords: Election, Printing, Strategy, Marketing, Media.